Understanding the Impact of Omega-3 Rich Diet on the Gut Microbiota. (14th March 2016) - Noriega, Blanca S.; Sanchez-Gonzalez, Marcos A.; Salyakina, Daria; Coffman, Jonathan
Abstract : Background . Recently, the importance of the gut microbiota in the pathogenesis of several disorders has gained clinical interests. Among exogenous factors affecting gut microbiome, diet appears to have the largest effect. Fatty acids, especially omega-3 polyunsaturated, ameliorate a range of several diseases, including cardiometabolic and inflammatory and cancer. Fatty acids associated beneficial effects may be mediated, to an important extent, through changes in gut microbiota composition. We sought to understand the changes of the gut microbiota in response to an omega-3 rich diet. Case Presentation. This case study investigated changes of gut microbiota with an omega-3 rich diet. Fecal samples were collected from a 45-year-old male who consumed 600 mg of omega-3 daily for 14 days. After the intervention, species diversity was decreased, but several butyrate-producing bacteria increased. There was an important decrease in Faecalibacterium prausnitzii and Akkermansia spp. Gut microbiota changes were reverted after the 14-day washout . Conclusion . Some of the health-related benefits of omega-3 may be due, in part, to increases in butyrate-producing bacteria. These findings may shed light on the mechanisms explaining the effects of omega-3 in several chronic diseases and may also serve as an existing foundation for tailoring personalized medical treatments.